Handbook of research on information and cyber security in the fourth industrial revolution (Advances in Information Security, Privacy, and Ethics (AISPE) book series, 2018)
"This book explores the severity of the threats at personal, business, governmental and societal levels; as well as what can be done to enhance security at these different levels. It covers topics such as: malware, criminal and strategic hacking, botnets, innovative cyber-attacks, cyber terrorism, cybersecurity trends, cyber offensive and defensive capability, digital forensics, cloud security, mobile security"--